Why Don't You See Me?: Meeting the Mental Health Needs of Black Male Students. Issue 3 (3rd July 2021) - Walker, Larry
ABSTRACT: Black male students throughout the United States encounter a variety of school, community, and familial stressors. This includes exposure to Adverse Childhood Experiences (ACEs) which impacts their socio-emotional growth and academic outcomes. For this reason, the article explores extant literature and offers actionable steps to prepare preservice teachers to meet the needs of Black male students. Specially, the author 1) explores the challenges Black male students encounter which impacts their mental health outcomes; 2) investigates how race impacts teachers' perceptions and attitudes and 3) identifies actionable steps teacher training programs should implement.